THE ROLE OF WRITTEN SOURCES IN THE STUDY OF HISTORICAL METROLOGY (American Journal of Technology and Applied Sciences, 2022)
The article is devoted to the role of written sources in the study of historical metrology. The development of historical metrology in Europe and the East.